Coarsening kinetics and strengthening mechanisms of core-shell nanoscale precipitates in Al-Li-Yb-Er-Sc-Zr alloy. (20th January 2021) - Wang, Yang; Zhang, Shun; Wu, Ruizhi; Turakhodjaev, Nodir; Hou, Legan; Zhang, Jinghuai; Betsofen, Sergey
Abstract: The tailored nanoparticles with a complex core/shell structure can satisfy a variety of demands, such as lattice misfit, shearability and coarsening resistance. In this research, core-shell nanoscale Al3 (Yb, Er, Sc, Zr, Li) composite particles were precipitated in Al-2Li-0.1Yb-0.1Er-0.1Sc-0.1 Zr (wt%) alloy through the double-aging treatment, in which the core was (Yb, Er, Sc, Zr)-rich formed at 300 °C and the shell was Li-rich formed at 150 °C. The coarsening kinetics and precipitate size distributions (PSDs) of Al3 (Yb, Er, Sc, Zr, Li) particles aged at 150 °C previously aged at 300 °C for 24 h showed a better fit to the relation of < r > 2 ∝ kt and normal distribution, indicating that the coarsening of precipitates was controlled by interface reaction, not diffusion. The Orowan bypass strengthening was operative mechanism at 150 °C.